Research on the Path of Innovating the Talent Cultivation Model in Vocational Colleges under the Vocational Education Group Model - Sha, Yan (Transactions on Social Science, Education and Humanities Research, 2024)
This study aims to explore the innovative path of talent cultivation models in vocational colleges under the vocational education group model. Through analyzing the current situation of vocational education, the theory and practice of vocational education groups, and the current situation of talent cultivation models in vocational colleges, this paper proposes innovative ideas in resource integration and sharing, school-enterprise cooperation and industry-education integration, curriculum setting and teaching reform strategies, as well as the construction of teaching staff. These paths help optimize the talent cultivation model in vocational colleges, enhance students' innovative abilities and comprehensive qualities, and adapt to the new demands of social development.